Strategi Guru Memproteksi Radiasi Budaya Bebas dalam Akhlak Pergaulan Siswa Pada Era 5.0 di MA Riyadhussholihin Megang Sakti Musi Rawas - Miftahul Roif; Ahmad Suradi; Moch Iqbal (UIN Fatmawati Sukarno Bengkulu, 2021)
Madrasah Aliyah represent a platform for both general and religious education at the foundational and secondary levels. This thesis aims to elucidate the strategies employed by teachers to counteract the influence of free-culture radiation on student social morality. The study employs a qualitative descriptive research methodology. The research subject include the school principal, the ethic and moral education teacher, and the curriculum section head at MA Riyadhussholihin Megang Sakti Musi Rawas. Data collection methods encompass observation, interviews, and documentation, with data validity ensured through triangulation. Data analysis is conducted through data reduction, presentation, and conclusion formulation. The research findings indicate that the teachers’ strategies for addressing diverse ethical perspectives among students in the 5.0 Era at MA Riyadhussholihin Megang Sakti Musi Rawas involve five key strategies: First, assisting students in their learning processes. Second, providing opportunitiescfor students to develop and excel. Third, reinvorcing character education. Fourth, optimizing interactions between students and teachers. Fifth, employing modern educational media.Supporting and hindering factors influencing the effectiveness of these strategies in mitigating the impact of free-culture radiation on student social morality include: Supporting Factors: a) School and Teacher commitment. b) Parental Coopration. c) Prudent use of thecnology. d) Strengthening religious identity. e) Digital ethics education. Hindering Factors: a) The influence of social media. b) Demands of a dense curriculum. c) Students’ levels of acceptance and comprehension. d) Resource limitations. e) Levels of parental involvement.Keyword: Teacher Strategies, Free-Culture Radiation, Social Morality, 5.0 Era